PERBAIKAN FUNGSI TROFOBLAST PADA KADAR Î² hCG TIKUS BUNTING PREEKLAMPSIA PADA BAHAN BIOLOGIS TERSIMPAN PASCA PERLKUAN DENGAN SPIRULINA - A, Adhiono ,; K, Gondo H; I, Noer Kumala (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Preeclampsia is multisystem specific disorder in pregnancy. Preeclampsia has signed byincreased cytokine Interleukin-6 and ? hCG (human Chorionic Gonadotropin). Spirulina is green-bluealga has bioactive compound namely antioxidant, vitamin, mineral. And has benefit namelyantinflamation. The aim of this research was to know how spirulina influence to repair trophoblast inHcg concentration on rat pregnancy (biology material collecting). The type of this research is anexperimental laboratoric with post test only control group design. A total of 25 rats with pre-eclampsiamodels induced by Interleukin 6 are divided into 5 groups: the untreated control group, the positivecontrol group with Interleukin 6 induction for three days, the treatment group with a dose of 10 mg /day, 20 mg / day and 40 mg of spirulina. / day for five day, then the blood serum produced was measuredwith ? hCG levels using ELISA (Enzyme-Linked Immunosorbent Assay). The results of the Spirulina 10mg / day are higher at 85.11 ± 25.70 mIU / ml from a dose of spirulina 20 mg / day at 79.65 ± 10.65mIU / ml . In the level of ? hCG, the dose group of spirulina 10 mg / day and the group there is nosignificant difference (0.730> 0.05), the ? hCG level group of spirulina 40 mg / day was 93.28 ± 17, 12mIU / ml from the dose group of spirulina 10 mg / day was 85.11 ± 25.70 mIU / ml. The administrationof spirulina for five days was able to reduce ? hCG levels at a dose of 10 mg / day, 20 mg / day and 40mg / day and the dose that was most effective in reducing ? hCG levels significantly (P <0.05) was adose of 10 mg than dose of 20 mg / day and 40 mg / day.